Effects of High Fat Broiler Pre-starter Rations on Performance and Cost - Birk, A.R.; Johnson, C.A.; Firman , J.D. (International Journal of Poultry Science, 2016)
Background: Addition of fat has been shown to improve performance of broilers, but can also be expensive. Methodology: An experiment was designed to determine if early addition of fat might lead to performance improvements that would be maintained to market weight. Forty nine days experiment was conducted to test the addition of 6 or 8% Yellow Grease (YG) to diets of broilers during the 0-10 or 0-14 day pre-starter period. Forty eight pens of birds were fed one of 6 treatments of 8 pens (33 chicks per pen) consisting of a control (least cost addition of YG), 6% YG or 8% YG, each fed to either 10 or 14 days. Diets consisted of commercial type corn-soydistillers dried grains with solubles(DDGS)-meat meal base and were adjusted to maintain a consistent relationship between energy and crude protein as well as amino acids. Birds were weighed and diets changed at 10 or 14 days, 17 days and 35 days with completion of the trial at 49 days. Results: Feed conversion was significantly improved by the addition of fat during the treatment period, a result of numerically higher body weight and reduced feed intake, although neither was significant. Improved growth performance from the addition of fat during the treatment period did not result in improved performance at market, as no effects by dietary treatment were found at 49 days. Conclusion: These results suggest the addition of high levels of fat in the pre-starter ration does not improve growth performance at 49 days.